Tolerability of Erythrocyte Ribavirin Triphosphate Concentrations Depends on the ITPA Genotype. Issue 4 (August 2019) - Tanaka, Yoichi; Inoue, Akiko; Mizunuma, Tomohiko; Matsumura, Haruka; Yokomori, Hiroaki; Komiyama, Takako; Otori, Katsuya
Abstract : Background: Ribavirin (RBV) is an antiviral drug that is part of the current standard therapy for chronic hepatitis C (CHC). It is enzymatically converted to ribavirin triphosphate (RTP) that inhibits the activity of viral RNA polymerase, thereby preventing viral replication. However, one of its adverse effects includes hemolytic anemia that limits its application. The variant of ITPA (inosine triphosphatase), which dephosphorylates inosine triphosphate to inosine monophosphate, is a protective factor for RBV-induced anemia. RTP is an important metabolite required for ribavirin action. This study evaluated the time-dependent association of RTP concentrations in erythrocytes, RBV-induced toxicity, and virological response to RBV treatment for hepatitis C. Methods: A total of 28 Japanese patients with CHC were treated with RBV/peg-interferon/simeprevir or RBV/sofosbuvir and were genotyped for ITPA variants ( rs1127354 and rs7270101 ). We measured RTP concentrations in erythrocytes in a total of 76 samples collected at 4, 8, and 12 weeks from the initiation of treatment. Results: The ITPA rs1127354 variant was found in 7 patients. This was associated with significantly higher RTP concentrations in erythrocytes than in the wild-type patients ( P < 0.001). Moreover, a significant correlation was observed between RTP concentrations and decline in hemoglobin (Hb) levels from baseline values in ITPA wild type and rs1127354 variant 12 weeks after treatment initiation ( P < 0.01; r = −0.618 and −0.967, respectively). Multiple regression analysis revealed that ITPA genotype and erythrocyte RTP concentrations were major factors associated with reduced Hb levels in RBV therapy for CHC. However, we did not find any association between erythrocyte concentrations and virological response. Conclusions: The increased tolerability to RTP concentrations in erythrocytes in the ITPA variant rs1127354 plays a role in preventing RBV-induced severe anemia in this ITPA variant.